An acoustic performance analysis of AC-motor bathroom ventilation fans for a decade-long period, 2005–2015. (3rd October 2017) - Choi, Wongyu; Pate, Michael B.; Sweeney, James F.
Abstract : The most common HVAC device in a residence, or in most other buildings for that matter, is the bathroom ventilation fan. Because these devices operate in close proximity to humans, the concept of loudness is particularly relevant to the acoustic performance of fans. In this regard, acoustic performance is an important component of indoor environmental quality, and the use of loudness as a method of achieving an acoustic rating is now widely accepted in codes and standards. Therefore, a long-term comparative study investigating changes in acoustic performances was performed for bathroom ventilation fans of the alternating current (AC) motor type, with a focus on fan loudness over an 11-year period from 2005 to 2015. Because of difference in performances and designs along with divisions created by testing standards and codes, the 1400 fans tested and analyzed were divided into low- and high-volume flow rate groups, namely below and above 42.5 L/s. In addition to specific conclusions reached from analyzing 11 years of fan performance measurements, major overall conclusions are that (1) the fan noise in terms of loudness has decreased, even to the point of being lower than typical human conversations in many cases, and (2) fan loudness has a weak relationship with volume flow rate and a more noticeable linear relationship with fan rotating speed. This study proves that acoustic performance improvements in bathroom ventilation fans have advanced acoustic-indoor environmental quality over the decade-long period of this study.